Pandangan Masyarakat terhadap Fenomena Kehamilan Remaja di Luar Nikah di Kabupaten Alor - Munawir A Dakamoli (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
This study aims to understand community perceptions regarding teenage pregnancy out of wedlock in Alor Regency, East Nusa Tenggara. Using a qualitative research approach, data were collected through in-depth interviews, field observations, and documentation. The participants included community leaders, religious figures, parents, and adolescents who experienced out-of-wedlock pregnancy. The results indicate that the community views teenage pregnancy out of wedlock as behavior that violates religious, social, and cultural norms. This phenomenon is considered a source of shame for families and communities, leading to social stigma. The main factors contributing to this issue include weak parental supervision, negative peer influence, and insufficient sexual education among adolescents. Preventive efforts involve strengthening moral and religious education, enhancing parental control, and improving educational facilities through local government initiatives. This research is expected to serve as a reference for communities and educational institutions to reduce the rate of teenage pregnancies in rural areas.